The analysis and quantifiaction of uncertainty for least life-cost electrical low voltage distribution design - Heunis, Schalk W. (Schalk Willem) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2000.